The taxation of non-resident entertainers and sportspersons - Sudding, Creagh (Department of Commercial Law, 2014)
In the ever expanding world of sports and entertainment a lot of money circulates amongst artistes, entertainers and sportspersons. This is of great economic relevance given the fact that, as with any business activity, the resources of the country in which they perform are used to earn these monies; as such these countries should have a right to reap some form of payment, through taxation, for the use of their resources. Given the large quantum circulating amongst these performers, it is a fairly lucrative source of economic revenue for the respective countries' tax authorities. In South Africa it is of considerable importance that the Commissioner of SARS (CSARS) ensures that he has access to this form of tax revenue, especially given the fact that the recent growth in the sports and entertainment industries in South Africa have been greater than the rest of the world. As such the CSARS must ensure these performance incomes form part of his tax base. Not only have international musicians and artistes taken a liking to touring and performing in South Africa, but the awarding of the right to host various Sports' World Cups are also significant contributors to this increasing tax base. As we are dealing with the taxation of non-residents in South Africa, the focus of this paper is within the realms of international law, specifically dealing with international tax practice. There is no international tax act governing International tax practice, as such it is more customary law based and is derived from the international tax agreements entered into between countries in order to clarify which country has the right to tax certain forms of income earned by a resident of either contracting country. More specifically with regards to international artistes, entertainers and sportspersons the current practice is to tax these performers on the income received from their performances in the country of performance. The CSARS also follows this practice, but due to practical difficulties, the taxation of these performance incomes is not as effective as it should be, in turn eroding the CSARS's tax base. This loss of tax revenues has lead to the recent introduction of Sections 47A - 47K, effective from 01 August 2006, in the South African Income Tax Act No. 58 of 1962, to try and mitigate these losses. Each year these losses of revenues continue to increase, and given the future growth of these revenues in South Africa, particularly looking towards the 2010 Soccer World Cup, the CSARS needs to ensure they try and minimise these losses. According to Grant Thornton the 2010 World Cup is expected to earn ZAR7.2 Billion in taxes , so should the CSARS not have effective legislation in place, they could sacrifice a large proportion of these prospective revenues; this is a material amount of money to throw away due to practical ineffectiveness. The focus of this paper is therefore to evaluate whether the new legislation will in fact help towards improving the CSARS's ability to collect his revenues from the use of South African resources by international performers. This paper is an interpretive guide to the practice of the taxation of non-resident artistes, entertainers and sportspersons in South Africa. There is no greater focus on the artiste, the entertainer or the sportsperson as they are rather seen as one for the purposes of this paper and as such will be collectively referred to as performers. This paper takes the following approach in reaching a conclusion on whether the new South African Tax Legislation, S47A S47K, will be effective in the taxation of non-resident performers in South Africa: Current international practice Double Tax Agreements and the OECD and UN Taxation Model Conventions Article 17 Current Issues/Problems The Definitions 1. Sportsmen 2. Residence 3. Performer 4. Source 5. Performance Income The Deductibility of Performance Expenses Elimination of Double Taxation and Non-Discrimination Explain current practice in South Africa Prior to the new legislation: Practice, Issues and Problems The new legislation Conclusion: Shortfalls and Recommendations